Identifying Factors Influencing Visionary Leadership: An Empirical Evidence from Thai Manufacturing Industry - Walailak Atthirawong; Wariya Panprung (My University, 2021)
Supply chain consists of all integrated activities that bring products to markets in the righttime, at the right place while creating value added in order to satisfy customers. Theperformance of all activities in the supply chain requires the cooperation and coordination ofcomplex processes across all members in organizations. Successful supply chainmanagement relies on great leaders, who can communicate with their supply chain membersand encourage feedback systems to improve the workplace environment. The leaders havethe principal goal of making use of modern, scientific, technical and innovative methods inthe implementation of tasks and activities. Therefore, the aim of this study was to investigatekey factors affecting visionary leadership in the context of Thai manufacturing industry.Data were collected using survey questionnaires administered to supply chain managers ineach manufacturing company located in industrial estates across the country. A total of 500valid questionnaires were received and analyzed using structural equation modeling. Theresults revealed that communication skill had the highest impact on visionary leadership,followed by organization climate and creativity. The study outcome could be to the benefitof managers, who strive to generate visionary leadership and realize how important it is toincorporate communication skills as one of the most powerful instruments to improveleadership
Keywords: Manufacturing; Quality and Supply Management